Implementasi Model Pembelajaran Contextual Teaching and Learning Terhadap Hasil Belajar Siswa - Silvia Anggraini, Kiky Chandra; Aulia, Inarotul (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2023)
This study aims to determine the application of the contextual teaching and learning model to student learning outcomes in thematic learning. The type of research used is descriptive qualitative. The data collection technique uses observation sheets, interview guidelines and documentation. The data analysis technique used in this research is data collection, data reduction, data presentation, and conclusion drawing. The results showed that the contextual teaching and learning model in thematic learning was able to make students have the character of social care, have the ability to analyze symbols and meanings about Pancasila, and have the ability to communicate, ask questions and argue well. With the application of contextual teaching and learning models can improve learning outcomes from the affective, cognitive and cognitive domains of students.